Edukasi Pelayanan Kebidanan Dalam Pemberian MPASI Sehat Bergizi Sebagai Upaya Pencegahan Stunting di Kota Bukittinggi - Zilfi Yola Pitri; Lubis, Kholilah; Nova H, Desri (Universitas Sumatera Barat, 2024)
The results of the Basic Health Research in 2018 show that the prevalence of stunting in Indonesia is 30.8%. This figure is still quite far from the WHO target of 20%. The cause of stunting is known to be due to the lack of intake absorbed by the body, both intake since the womb and after birth, so that it can cause malnutrition. One of the factors that influence malnutrition is the lack of public knowledge of healthy lifestyles and the fulfilment of optimal nutrition. One of the efforts to fulfil good nutrition from an early age is by giving complementary food at the age of 6-24 months appropriately. The purpose of this community service activity is to educate women of reproductive age and mothers of infants about the provision of proper, cheap, and nutritious complementary food based on local food for stunting prevention. The targets in this activity are 45 mothers who have children aged 6 months - 2 years or women of reproductive age in Kalisari Village, Natar District, South Lampung. The methods applied in this counselling activity include: 1) measurement of knowledge about complementary food and how to give it; 2) counselling about complementary food; 3) discussion and question and answer; 4) final evaluation. This service activity was carried out on 15 March 2024. Counselling on complementary feeding and the use of local food ingredients as an appropriate source of complementary food as an effort to prevent stunting needs to be held regularly, so that mothers' knowledge about complementary feeding and the use of local food ingredients can be improved.